2018
DOI: 10.3389/fmicb.2018.02155
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Photobacterium damselae subsp. damselae Outbreaks in Marine Rainbow Trout Farms Reveals Extensive Horizontal Gene Transfer and High Genetic Diversity

Abstract: The marine bacterium Photobacterium damselae subsp. damselae is a pathogen for a variety of marine animals, as well as for humans, and is nowadays considered an emerging pathogen for fish of importance in marine aquaculture. Recent studies have suggested that outbreaks in fish farms are caused by multiclonal populations of this subspecies that exist in the environment. Here, we report the study of a collection of 31 strains isolated during the course of disease outbreaks in marine rainbow trout farms in Denmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 60 publications
(119 reference statements)
1
30
0
Order By: Relevance
“…Phylogenetic analysis based on the ToxR gene alone has demonstrated a multiclonal population of P. damselae subsp. damselae isolates that caused disease outbreaks in rainbow trout ( Oncorhynchus mykiss ) in Denmark from different years (Terceti et al, 2018). Interestingly, the strains clustered together using ToxR gene sequencing analysis shared the same biotypes as described in previous study (Pedersen, Dalsgaard, & Larsen, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis based on the ToxR gene alone has demonstrated a multiclonal population of P. damselae subsp. damselae isolates that caused disease outbreaks in rainbow trout ( Oncorhynchus mykiss ) in Denmark from different years (Terceti et al, 2018). Interestingly, the strains clustered together using ToxR gene sequencing analysis shared the same biotypes as described in previous study (Pedersen, Dalsgaard, & Larsen, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An extensive study that analyzed 71 Pdd isolates from fish in Spain, reported that 4% were sucrose-fermenters [28]. In another study with Pdd strains from disease outbreaks in marine rainbow trout, one isolate out of 31 tested positive for sucrose fermentation [24]. A study reported the simultaneous isolation on a TCBS agar plate of yellow and green Pdd colonies from different organs of the same fish [29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 8 Pdd strains contained a scr gene cluster. Of these, six were isolated from European seabass in the Black Sea [30], one from diseased rainbow trout in Denmark [24,37] and one from gilthead seabream from unknown geographical origin (Table 1). In order to ascertain whether the sucrose positive strains conform a clonal entity or whether the scr clusters have been acquired by different genetic lineages of Pdd, we carried out a comparative analysis of 23 complete Pdd genomes.…”
Section: Scr Clusters Occur In Different Genetic Lineages Of Pddmentioning
confidence: 99%
See 2 more Smart Citations